BUSINESS ACTORS’ SATISFACTION LEVEL IN OBTAINING PSAT-PDUK DISTRIBUTION PERMIT REGISTRATION IN GRESIK REGENCY - Farikhah Linda Aurantifolia; Teguh Soedarto; Hamidah Hendrarini (RADJA PUBLIKA, 2025)
This study aims to analyze the level of satisfaction among micro and small business actors in obtaining the PSAT-PDUK distribution permit in Gresik Regency. The research focuses on four main indicators: ease of registration process, service speed, officer performance, and administrative costs. Using a qualitative descriptive approach with purposive sampling, the study finds that the digital-based Online Single Submission (OSS) system effectively reduces bureaucratic barriers and enhances accessibility. The clarity and user-friendliness of registration forms, combined with ongoing assistance from local government agencies, support inclusive service delivery. Additionally, the speed of document verification and license issuance aligns with public service standards, reinforcing user trust. Officers’ interpersonal skills, technical competence, and informative communication contribute significantly to service quality and stakeholder satisfaction. The study also confirms that there are no hidden fees or illegal levies in the registration process. The PSAT-PDUK registration is officially free, although technical compliance costs such as lab testing and packaging remain the responsibility of the business actors. Transparency regarding these cost elements fosters trust and supports a corruption-free bureaucracy. Overall, the research highlights the success of the government in creating an efficient, accessible, and transparent permit system that supports the formalization and competitiveness of local fresh food businesses. However, sustained improvement through continuous user support and digital literacy enhancement remains necessary to ensure equal access across all business levels.